Effects of Dietary n-3 Rich PUFA Mixture on Performance, Plasma Metabolites and Muscle Fatty Acids Profile in Growing Pigs - Anca Gheorghe; Mihaela Hăbeanu; Nicoleta A. Lefter; Lavinia Idriceanu (Scientific Papers Animal Science and Biotechnologies, 2023)
The study was conducted to assess the effect of feeding an n-3 PUFA-enriched diet on growth performance, plasma metabolites, and muscle fatty acids composition in growing pigs. Forty growing pigs (13.1±1.8 kg body weight) were randomly divided to receive a control [C based on corn-triticale-soybean meal (SBM)] or n-3 PUFA mix diet [extruded linseed EL: walnut meal WM, where the 80 g/kg dietary mixture (50:30 wt/wt) partially replace SBM] for 30 days. At the end of the trial, blood and muscle samples were collected for plasma profiles and fatty acids analyses. Feeding pigs with n-3 PUFA-enriched diet slightly improved body weight and average daily gain (P>0.05) with similar feed intake, and tend to improve feed efficiency (P=0.058). There was no effect on plasma protein profile, but the plasma urea nitrogen was decreased (P=0.042) indicating a higher utilization of dietary nitrogen. Plasma lipid profile was affected as a response to the dietary mixture by reducing the total cholesterol concentration (P=0.04) vs C diet. The Longissimus Dorsi muscle of pigs fed dietary mixture had higher contents in alpha-linolenic acid (P=0.030), docosahexaenoic (P=0.050), total PUFA (P=0.0001) and n-3 PUFA (P=0.019), and a lower n-6: n-3 ratio (P=0.002) vs pigs fed C diet. In conclusion, the dietary mixture had a positive effect on growing pigs’ performance and health status, improving the plasma lipo-protein response and enhanced the fatty acid profile of the meat.